A Comprehensive Light-curve Model of the Very Fast Nova V1674 Herculis - Mariko Kato; Izumi Hachisu; Hideyuki Saio (The Astrophysical Journal, 2025)
V1674 Her is one of the fastest novae, of which the very early phase is well observed, including optical rise to the peak over 10 mag. We present a full theoretical light-curve model of V1674 Her. Our 1.35 M _⊙ white dwarf (WD) model with the mass accretion rate of 1 × 10 ^−11 M _⊙ yr ^−1 explains overall properties including a very fast rise and decay of the optical V light curve. The WD photosphere expands up to 21 R _⊙ , thus a 0.26 M _⊙ companion star orbiting the WD every 3.67 hr is engulfed 2.7 hr after the onset of thermonuclear runaway and appears 5.3 days after that. The duration of X-ray flash is only 0.96 hr. The evolution of the expanding envelope and temporal change of the photospheric radius are very consistent with observed optical and X-ray modulations with the orbital and spin (501 s) periods. We confirm that the decay phase of the nova light curve is well approximated by a sequence of steady-state envelope solutions. Using the time-stretching method of nova light curves, we obtain the V -band distance modulus of ( m  −  M ) _V  = 16.3 ± 0.2 and determine the distance to be d  = 8.9 ± 1 kpc for the interstellar extinction of E ( B – V ) = 0.5 ± 0.05.